IMPLEMENTASI PERATURAN DAERAH NOMOR 02 TAHUN 2011 TENTANG PENGELOLAAN SAMPAH DI DINAS KEBERSIHAN DAN PERTAMANAN (DKP) KOTA SAMARINDA - Siti Rachmah (Jurnal Paradigma (JP), 2017)
The purpose of this study is to analyze the implementation of the Regional Regulation Samarinda No. 02 of 2011 on Waste Management in the Department of Hygiene and City Park (DKP) Samarinda and to explain the supporting and hindering factors in the implementation. This research is a descriptive studies and analyzed qualitatively. From the results of research can be concluded that the implementation of the Regional Regulation Samarinda No. 02 of 2011 on Waste Management by DKP Samarinda is not running optimally, it can be seen from the implementation of socialization that has not been evenly distributed in society, product marketing recycling bins residents who have not been accommodated well, the condition of the fleet is inadequate, kekurangaktifan ramli bank and the provision of polling stations yet to reach areas far from the city center so there are still people who have not been reached by the services of cleanliness by DKP Samarinda.